Psychopharmacology for Patients with Parkinson’s Disease and Deep Brain Stimulation: Lessons Learned in an Academic Center - Seritan, Andreea L.; Ureste, Peter; Duong, Tammy; Ostrem, Jill L. (Current Psychopharmacology, 2019)
Background: Deep brain stimulation (DBS) is a modern neuromodulation method used in the treatment of advanced movement disorders such as Parkinson’s disease (PD) and dystonia. Patients with PD may have multiple psychiatric comorbidities, notably anxiety, depression, mania or hypomania, and psychosis. DBS surgery may indirectly alleviate psychiatric symptoms by allowing reduction of dopaminergic medications, or as a result of functional improvement. Patients who are considering DBS for PD often have more advanced disease and may be more vulnerable to perioperative psychiatric decline. Albeit infrequently, increased depression, apathy, irritability, hypomania or mania, and suicidal behavior have been observed after DBS surgery. Objective: This review aimed to present current evidence and empirical recommendations for the management of the psychiatric symptoms in patients with PD treated with DBS. Method: Relevant literature was reviewed and synthesized, along with recommendations informed by the authors’ clinical experience in a large, academic DBS center. Results: Careful evaluation of DBS candidacy, including assessing the risk for perioperative psychiatric decompensation is advised. Maintaining at least eight weeks of psychiatric stability prior to DBS surgery is strongly recommended. Postoperative management can be challenging due to advanced disease, concurrent psychiatric comorbidities, and possible DBS stimulation-related effects on mood and impulse control. Stimulation-induced elevated mood states (mania, hypomania) have started to be recognized as distinct clinical entities, although not included in the current psychiatric nomenclature. Conclusion: Insufficient evidence-based strategies for managing psychiatric symptoms in PD patients with DBS exist at this time. Further research is necessary to uncover best practices in this complex, expanding field.
Keywords: Parkinson' s disease